Ribonucleases. possible new approach in cancer therapy - Shlyakhovenko, V.O. (Experimental Oncology, 2016)
In the review, the use of the ribonucleases for cancer therapy is discussed. Using of epigenetic mechanisms of regulation — blocking protein synthesis without affecting the DNA structure — is a promising direction in the therapy. The ribonucleases isolated from different sources, despite of similar mechanism of enzymatic reactions, have different biological effects. The use of enzymes isolated from new sources, particularly from plants and fungi, shows promising results. In this article we discuss the new approach for the use of enzymes resistant to inhibitors and ribozymes, that is aimed at the destruction of the oncogene specific mRNA and the induction of apoptosis.